Braindead - King, Michelle 1958-; King, Robert 1959- (CBS Studios, 2016)
When struggling documentary filmmaker Laurel Healy takes a job working with her brother, Senator Luke Healy, she soon discovers there's more to Washington than meets the eye. As tensions grow amongst political parties, so does a conspiracy involving alien bugs replacing the brains of several members of congress. The investigation unfolds while the infection spreads. Whatever's happening, it's clear this isn't politics as usual
Staffel 1
TV-Serie. USA. 2016
Keywords: Television series; Fernsehserie; Legislators / United States / Drama; Extraterrestrial beings / Drama; Opposition (Political science) / United States / Drama; Washington (D.C.) / Drama; Extraterrestrial beings; Legislators; Opposition (Political science); United States; Washington (D.C.); DVD-Video discs; Video recordings for the hearing impaired; Television programs for the hearing impaired; Television comedies; DVD-Video